Respatialization and local protest strategy formation: Investigating high-speed rail megaproject development in the UK. (February 2015) - Rozema, Jaap G.; Cashmore, Matthew; Bond, Alan J.; Chilvers, Jason
Highlights: Spatialization processes are critical for understanding protest strategy formation. Respatialization concerns reframing protest according to a new spatial conception. In the HS2 case local protest was respatialized to focus on national economic issues. Local actors may detach from 'place' in protest assemblages. Spatialities help give insight into the geographies of social action. Abstract: Understanding spatial conceptions is critical to the analysis of local protest strategy formation. Spatialities provoke inquiry into the drivers that may prompt local actors to adhere to particular strategies, and the implications this has on forms of contestation and the way protest is organized. It is argued that local protest can 'respatialize' when actors are embedded in social movements and translocal assemblages associated with controversy over development, and that this warrants reconsidering the role of 'place'. A case study of a proposed megaproject framed in the national interest – a high-speed rail network called HS2, in the United Kingdom – is used to investigate local protest respatialization. Fieldwork was conducted in the Chilterns, an area of high scenic beauty which will be adversely impacted by HS2. The results show how the perceived need to respatialize protest away from the local to the national domain reconfigures debate to focus primarily on economic issues. Respatialization also has implications for the dynamics of protest assemblages with unlikely alliances developing around a need to engage with or engender debate in the national polity. It is concluded that local actors may opt to respatialize their protest in response to their interaction with social movements and protest assemblages that disengage from specific place-based interests. The paper recommends that future research on the geographies of social action take forward spatialization as a powerful lens for investigating protest strategy formation.